Static Output Feedback Control for Discrete-Time Switched Systems via Improved Path-Following Method. (11th October 2015) - Chen, Jian; Lin, Chong
Abstract : This paper focuses on the problems of static output feedback control andH ∞ controller design for discrete-time switched systems. Based on piecewise quadratic Lyapunov functions and a new linearization method, new sufficient conditions for system stability andH ∞ controller design are obtained. Then, an improved path-following algorithm is built to solve the problems. Finally, the merits and effectiveness of the proposed method are shown by two numerical examples.